Tourism Vocational High School Students' Online EFL Learning Experience during Covid-19 Pandemic - Prasetio, Eka; Priyana, Joko (Jurnal Pendidikan dan Pengajaran, 2021)
The unique nature of ESP instructions that mainly focuses on practical use of English and the lack of previous studies in the area inspired the writers to investigate the tourism VHS students' experience when they conducted online EFL learning during the COVID-19 pandemic. This study aims to explore the tourism vocational high school (VHS) students' experience of EFL learning during the COVID-19 pandemic. A qualitative study was utilized to obtain 20 students' experience. The data were obtained from grades 10 and 11 students of tourism VHS in Yogyakarta. A semi-structured interview was conducted, and verbatim transcripts were analyzed using inductive and thematic analysis approaches. Three major themes were identified from the students' experiences, namely how they conducted the EFL teaching and learning; language learning strategies; and perceptions of online EFL learning. It was found that students have made use of all available resources. This study suggests that students have used appropriate language learning strategies for online EFL learning, such as cognitive, metacognitive, resource management, and social strategies. Their perceptions toward EFL online learning were mainly positive. However, students still prefer face-to-face learning to online learning.